Memory, history, nation, war : the official histories of New Zealand in the Second World War, 1939-45 : a thesis presented in fulfilment of the requirement of the Doctor of Philosophy in History, Massey University, Palmerston North, New Zealand - Bell, Rachael Elizabeth (Massey University, 2012)
The Official Histories of the Second World War are the largest historiographical project in New Zealand's history. They are still used as core reference texts for individual battles and for the war as a whole. The War Histories were intended to fill a wide range of roles. They were to be 'at once a memorial, a souvenir, an interpretation of events and a record of experience in certain specialised fields'. The conflicting nature of these roles created a double dichotomy within the War History project, between an affirmative national memory and an empirically accurate history on the one hand and between the critical evaluation of campaigns and the recognition of service and sacrifice on the other. This thesis examines this dichotomy through a framework of memory, history, nation and war. It uses four case studies from the War History series, Journey towards Christmas, by S.P. Llewellyn, 23 Battalion, by Angus Ross, Crete , by Dan Davin and Battle for Egypt, the Summer of 1942, by J.L. Scoullar, to consider the extent to which the tensions between the roles of the Histories influenced their production and their place as contemporary histories in post-war New Zealand. While the War Histories represent the largest repository of information on New Zealand in World War Two, the thesis contends that to use the series now as reference works only is to miss a significant opportunity. The War Histories were Official, but they were also contemporary and collective in their production. Each volume in the series is a valuable historical text in its own right, and can be read and deconstructed as representative of both the individual and society that produced it.
Keywords: Second World War; World War II; New Zealand; Historiography; History; Histories; War histories